Validity test of the Global Leadership Initiative on Malnutrition (GLIM) diagnostic criteria compared with the American Society for Parenteral and Enteral Nutrition (ASPEN) criteria in inpatients at Dr. Cipto Mangunkusumo hospital: A cross-sectional study - Oentiono, Oki Yonatan; Manikam, Nurul Ratna Mutu (Indonesian Nutrition Association, 2024)
Background: Malnutrition experienced by numerous inpatients is linked to various complications. The Global Leadership Initiative on Malnutrition (GLIM), which established the latest malnutrition criteria, recommends a two-step methodology for diagnosing malnutrition in adult inpatients. This study aims to evaluate the validity of the GLIM criteria for the diagnosis of malnutrition in hospitalized patients at Cipto Mangunkusomo Hospital Jakarta by comparing them with the ASPEN criteria. Methods: This cross-sectional study was conducted at Cipto Mangunkusomo Hospital, Jakarta. Secondary data was taken from 100 inpatients from October 2021 to February 2022 selected by consecutive sampling technique. The diagnosis of malnutrition in the patients applied the ASPEN and GLIM criteria. Furthermore, data were analyzed using Cohen's Kappa and chi-square tests. Results: Of 100 inpatients, 63% were diagnosed with malnutrition according to the GLIM diagnostic criteria. Meanwhile, 48% of them were found to be malnourished according to the ASPEN criteria. The GLIM criteria have a specificity of 69.2%, a sensitivity of 97.9%, a PPV of 74.6%, and an NPV of 97.3%. Conclusion: The GLIM diagnostic criteria are valid as an instrument for diagnosing malnutrition but require further research to assess the severity of malnutrition.